The omen - Williamson, Glenn; Seltzer, David, 1940-; Moore, John, 1970-; Stiles, Julia; Schreiber, Liev; Farrow, Mia, 1945-; Thewlis, David, 1963-; Postlethwaite, Pete; Gambon, Michael; Davey-Fitzpatrick, Seamus, 1998-; Radice, Giovanni Lombardo, 1954-; Sela, Jonathan, 1978-; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2006)
Robert and Katherine Thorn are as loving of parents as any young boy could ask for, but as fate would have it, their new son Damien is far from the typical child. As the mysterious boy's growth begins to share frightening parallels with the Biblical passages detailing the rise of the Antichrist, and the lives of all who seek to reveal his true nature are cut gruesomely short, Robert and Katherine are forced to face the horrifying prospect that their child has been sent from Satan to hasten the fall of modern civilization, and that there is little they can do to curb his prophesied path of ultimate destruction.
Dual layer.
Special features: Never-before-seen alternate ending; Extended scenes; Director commentary; featurettes.
Originally released as a motion picture in 2006.
Music by Marco Beltrami ; film editor, Dan Zimmerman ; production designer, Patrick Lumb ; director of photography, Jonathan Sela ; executive producer, Jeffrey Stott.
Julia Stiles, Liev Schreiber, Mia Farrow, David Thewlis, Pete Postlethwaite, Michael Gambon, Seamus Davey-Fitzpatrick, Giovanni Lombardo Radice.
MPAA rating: R; for disturbing violent content, graphic images and some language.
Keywords: Omens -- Religious aspects -- Drama; Parent and child -- Drama; Prophecy -- Drama; Good and evil -- Drama; Fiction films; Video recordings for the hearing impaired; Feature films; Horror films